EDUKASI PEMBUATAN HAND SANITIZER BAGI MASYARAKAT KELURAHAN LILIBA KOTA KUPANG - Marianus Jefri Agang; Timotius Nesanto; Aloysius M. Kopon; Maria Benedikta Tukan; Anselmus Boy Baunsele; Maria Aloisia Uron Leba; Faderina Komisia; Erly Grizca Boelan; Yustina D. Lawung (Politeknik Negeri Sriwijaya, 2021)
The increasing of Covid-19 spread is certainly a challenge for the community in incounter of COVID-19 pandemic. The implementation of health protocols and public understanding about COVID-19 must to be improved. One form of health protocol is the hand sanitizers utillization. Hand sanitizer can be bought at by various prices. The availability of natural abundance is the basis reason for innovations to be produce the hand sanitizers. Educational activities for the hand sanitizers produce made from betel leaf and aloe vera in the Liliba sub-district, of Kupang city using the video and YouTube as well as socialization to the community aims to provide information for the community to utiliize the natural ingredients to create the hand sanitizers. This is carried out to support the implementation of health protocols. The selection of video tutorial media is because the community can be widely access. In addition the other activities socializing about the hand sanitizers produce and distributing the home made hand sanitizer products. The socialization involved the Liliba sub-district Covid-19 team. The hand sanitizers that have been produced by practical students of chemistry educational study program of Widya Mandira University are then distributed to the audience of the socialization. The hand sanitizer production brochure distributed to the public as a simple way of academics contributing ideas to help the community on COVID-19 pandemic.